The Social Consequences Of Religious Communication In Ghana's Digital Space. - Adasi, G.S. (The Trinity Journal of Church and Theology, 2025)
The research focuses on the rise of misleading and false theologies/doctrines propagated through social networking sites, specifically emphasising the neo-prophetic wing of Pentecostalism in Ghana. The study employed an exploratory research design that included quantitative and qualitative methods. The study investigated the influence of modern Ghanaian prophetic ministries on people's religious attitudes and their integration into society. Some examples are false teachings that are readily available online, for example, the prosperity gospel, spiritual warfare narratives, sensationalised prophecies, etc. It emerged from the research that such teachings have great impact on what individuals believe in, how they act and even the decisions they make. This situation normally makes them vulnerable to people who take advantage of them economically and manipulate them psychologically. The study revealed that such teachings pose serious threats of public disunity, consumerism and low political participation, among others. The transformation brought about by the digital age of new prophetic movements offers an avenue for both positive and negative influences on spirituality. Various measures have been taken by civil society groups together with governmental agencies, such as conducting public education and enacting relevant laws; however, promoting critical thinking and media literacy turns out to be an effective way of dealing with misinformation.
Research Article
Keywords: Misleading Theologies/Doctrines; Social Media Platforms; Ghana; Neo-PropheticMovements; DigitalReligion.